Analisis Kasus Pelanggaran Merek Milo-Camilo dan Dampaknya Bagi UKM Indonesia - Uwaisi Mubarok Sandy; Romi Faslah (CV. ITTC INDONESIA, 2025)
Background: Trademark infringement cases increasingly threaten Small and Medium Enterprises (SMEs) in Indonesia, affecting business identity, competitiveness, and financial security. The Milo and Camilo case demonstrates how similar brand names can confuse consumers and harm legitimate businesses. Objective: This research analyzes the impact of trademark infringement on SMEs, examines legal protections, and offers recommendations for strengthening trademark awareness and safeguarding SME business identity. Method: The study adopts a normative juridical and case study approach, using literature reviews, case analysis, and Islamic legal perspectives on intellectual property and business ethics. Results: The findings reveal that Small and Medium Enterprises (SMEs) (1) suffer significant financial and reputational losses due to weak trademark (2) ownership and protection practices. Insufficient understanding and application of legal protection (3) frameworks increase SME vulnerability to market threats. Limited integration of Islamic law (4) principles in intellectual property rights weakens fair business ethics. Frequent infringement (5) cases like the Milo and Camilo dispute highlight the need for proactive trademark registration, legal literacy, and effective dispute resolution. Conclusion: Strengthening trademark protection for SMEs requires improving legal awareness, applying consistent legal frameworks, and promoting ethical business practices based on Islamic law.